Development of Media Based Learning Google Sites to Improve PAI Learning Outcomes at SMPN 15 Malang - Umi Zahrotus Sa'adah; Zulfa Nailatul Husna; Imroatul Lathifa; Nadhiya Noor Thoyyibah; Sutiah Sutiah (Universitas Muhammadiyah Enrekang, 2023)
Google sites is a website media that can be used in the learning process, group or personal. The aim of this research is to find out: 1) Developing a Google Sites-based learning media design for PAI learning, 2) How appropriate a Google Sites-based learning media design is for PAI learning. 3) What is the appeal of Google Sites-based learning media design for PAI learning? The research approach used in this research is Research and Development (RnD). The result of this research is the development of Google Site-based learning based on the ADDIE model and is declared